Quercetin And Curcumin Prevent Decreasing Of LDL-Cholesterol And Increasing Of HDL-Cholesterol In High Fat Diet Rats - Harumi P, Made; Trisna, Gita; Odiyana P G, Nyoman; Aulia R, Deby; Khrisnawati, Putri; Farmawati, Arta (Universitas Ahmad Dahlan, 2015)
Cardiovascular disease is number one killer disease in the world. The most common etiology is atherosclerosis. LDL and HDL-cholesterol are often associated with atherosclerosis which are affected by diet. Quercetin and curcumin considered have influenced to LDL and HDL. They are antioxidant that protect against LDL oxidation and raised HDL-cholesterol. In this study, we invest about comparison effect of prevention in LDL and HDL level change, after giving quercetin and curcumin. 20 males Rattus novergicus rats in 200-300 grams divided into 4 groups. Group B, C, D were given high-fat diet for 4 weeks, while group A (negative control) was given standard woof. Group B was positive control and no treatment, C was given quercetin, D was given curcumin. The treatment and giving high-fat diet was done simultaneously to detect prevention effect. HDL and LDL-cholesterol evaluated two times, pre and post-treatment. Result showed the increase prevention level of LDL-cholesterol and decrease prevention level of HDL-cholesterol in group C and D significantly. The best prevention effect is quercetin, p=0.000. Furthermore, we showed there was no significant correlation between DLDL and DHDL-cholesterol level. In conclusion, quercetin and curcumin have a good effect in preventing hypercholesterolemia, however quercetin have better effect than curcumin. Keywords: quercetin curcumin, HDL-cholesterol, LDL-cholesterol